Perbandingan Tepung Talas Kimpul (Xanthosoma sagittifolium) Termodifikasi dan Tepung Kacang Merah (Phaseolus vulgaris) Terhadap Karakteristik Non-Flaky Crackers - Saragih, Anna Yasmin; Wiadnyani, Anak Agung Istri Sri; Rai Widarta, I Wayan (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 12 No 4 (2023): Jurnal ITEPADO - 10.24843/itepa.2023.v12.i04.p12, 2023)
Non-flaky crackers are crackers that are not layered inside. Generally, crackers which are made from wheat flour have a low fiber content, cocoyam autoclaving-cooling modified flour can be used as a substitute for wheat flour to increase dietary fiber. Cocoyam modified flour has a low protein content, so red bean flour needs to be added to increase protein content of crackers. The purpose of this study is to determine the effect of the ratio of modified cocoyam flour and red bean flour on non-flaky crackers and to obtain non- flaky crackers with the best characteristic. The research design of this study is completely randomized design with 5 treatment levels, 90:10, 80:20, 70:30, 60:40, and 50:50 repeated 3 times to obtain 15 experimental units. The data obtained was analyzed by ANOVA, then proceed with DMRT test. The results showed that the comparison of modified cocoyam flour and red bean flour had a significant influence (P<0,05) on chemical properties including water content, texture tests including hardness, fracture, crunchiness, chewiness, cohesiveness, color test including L*, a*, b*, browning index, hedonic test including color, texture, taste, overall acceptance. The best treatment was the comparison of 70% modified cocoyam flour and 30% red bean flour with hardness 75,70 N, fracture 4,87 N, crunchiness 37,50 Nmm, chewiness 27,88 N, cohesiveness 0,45, water content 2,71%, ash content 3,89%, protein content 9,74%, fat content 0,17%, carbohydrate content 83,49%, dietary fiber content 4,88%, resistant starch content 3,95%, browning index 68,55 (L* 48,00; a* 7,30; b* 34,83), the color is like slightly, the aroma is neutral, the texture is like slightly, the taste is like slightly, and the overall acceptance is like slightly.